Dari Tekstualisme menuju Kontekstualisme: Arah Baru Reformasi Kurikulum Pendidikan Islam di Indonesia - Nurhayati Ali; Imar Putra (Khulasah : Islamic Studies Journal, 2026)
Curriculum reform in Islamic education in Indonesia faces serious challenges amidst increasingly complex social, cultural and religious dynamics. To date, the Islamic education curriculum has remained dominated by a textualist approach that emphasises a literal understanding of religious texts and tends to overlook the historical context and social realities of the learners. This article aims to analyse a new direction for the reform of the Islamic education curriculum through a paradigm shift from textualism towards contextualism. This article employs a qualitative approach using critical literature review and discourse analysis of curriculum documents, journal articles, and academic literature from the past seven years. The research findings indicate that whilst the discourse on contextualism is growing within academic studies, its implementation in the national curriculum remains partial and lacks systematic integration. The dominance of the textualist paradigm continues to limit the development of students’ critical thinking and social awareness. Therefore, this article emphasises the importance of an epistemological paradigm shift in the reform of the Islamic education curriculum. Contextualism must be positioned as a guiding principle in the formulation of objectives, the development of teaching materials, and evaluation strategies so that Islamic education can shape a generation of Muslims who are religious, critical, moderate, and socially responsible